Beyond the Divide: Boundaries for Patterning and Stem Cell Regulation in Plants - Hepworth, Shelley R.; Pautot, Véronique A. (Frontiers in Plant Science, 2015)
The initiation of plant lateral organs from the shoot apical meristem is closely associated with the formation of specialized domains of restricted growth known as the boundaries. These zones are required in separating the meristem from the growing primordia or adjacent organs but play a much broader role in regulating stem cell activity and shoot patterning. Studies have revealed a network of genes and hormone pathways that establish and maintain boundaries between the shoot apical meristem and leaves. Recruitment of these pathways is shown to underlie a variety of processes during the reproductive phase including axillary meristems production, flower patterning, fruit development, and organ abscission. This review summarizes the role of conserved gene modules in patterning boundaries throughout the life cycle.